Synthesis and Cytotoxicity of Dendritic Platinum Nanoparticles with HEK‐293 Cells. Issue 1 (2nd December 2016) - Shim, Kyubin; Kim, Jeonghun; Heo, Yoon‐Uk; Jiang, Bo; Li, Cuiling; Shahabuddin, Mohammed; Wu, Kevin C.‐W.; Hossain, Md. Shahriar A.; Yamauchi, Yusuke; Kim, Jung Ho
Abstract: Dendritic platinum nanoparticles (DPNs) have been synthesized froml ‐ascorbic acid and an amphiphilic non‐ionic surfactant (Brij‐58) via a sonochemical method. The particle size and shape of the DPNs could be tuned by changing the reduction temperature, resulting in a uniform DPN with a size of 23 nm or 60 nm. The facets of DPNs have been studied by high‐resolution transmission electron microscopy. The cytotoxicity of DPNs has been investigated using human embryonic kidney cells (HEK‐293), and the biological adaptability exhibited by DPNs has opened a pathway to biomedical applications such as drug‐delivery systems, photothermal treatment, and biosensors. Abstract : Not Toxic ! Dendritic platinum nanoparticles (DPNs) have been synthesized via a sonochemical method. The particle size and shape of the DPNs could be tuned by changing the reduction temperature, resulting in a uniform DPN with a size of 23 nm or 60 nm. The cytotoxicity of DPNs was investigated using HEK‐293 human embryonic kidney cells, and the biological adaptability exhibited by DPNs has opened a pathway to biomedical applications.